Peran Masyarakat Dalam Proses Diversi Tindak Pidana Anak Sebagai Upaya Mewujudkan Keadilan Restoratif - Imam Ahmad Ghozali (Empower : Jurnal Pengembangan Masyarakat Islam, 2020)
The Law of the Republic of Indonesia Number 11 of 2012 Concering Children's Criminal Court System, effective from July 31, 2014. This law can solve various issues of the children facing Law based on restorative justice principles. In the regulation it is discussed about diversion concept involving several parties and one of them is the community. This research aims to illustrate how community involvement and its operations in the implementation of the diversion as an attempt to create a restorative justice. The research method used is the juridical approach of empiris with qualitative analysis data. The research object is the completion of a child's criminal offence which is resolved through the diversion process. The results showed that the involvement of the society is not optimal in the process of diversion because it is influenced by several factors. That is a factor understanding restorative justice approach from the apparatus and society, factors of infrastructure and cultural law.